Interfacial characteristics, electrical conductivity, mechanical performance, and tribology behavior of ZrB2/Cu composites - Cong Li; Jing Shi; Bo Li; Weijia Ren; Zhen Cao; Lan Wei; Da Wu; Yimin Gao; Pucun Bai; Zhong Chen (Materials & Design, 2025)
The inferior anti-wear properties limited the service life and stability of the Cu materials in mechanical-electronic engineering fields. The ZrB2/Cu composites were prepared to optimize tribological and electrical properties based on the high hardness and low electrical resistance of ZrB2 ceramics. Introducing ZrB2 micro/nanoparticles significantly improved the Cu matrix’s hardness without severely reducing its electrical conductivity. Therefore, the electrical conductivity and hardness of the Cu-20 wt%ZrB2 composite were 20.18 %IACS and 231.64 HV, respectively. The compression strength of composites first improved and then decreased with the ZrB2 content. The lubrication characteristics offered by the continuous tribo-layer and the support effects of ZrB2 micro/nanoparticles were the primary reasons for enhancing friction reduction and anti-wear properties in Cu matrix composites. This work provided a theoretical foundation for the structural design of Cu-based composites with desirable electrical conductivity and wear resistance.